2021
DOI: 10.1136/gpsych-2020-100419
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological analysis of maladaptive daydreaming associated with internet gaming addiction: a case report

Abstract: Maladaptive daydreaming (MD) is an immersive fantasy activity that leads to distress and socio-occupational dysfunction. MD has many features suggestive of behavioural addiction, but research exploring the phenomenology of this clinical construct is limited. MD has also been purported to be a maladaptive strategy to cope with distress, but often leads to uncontrollable absorption in fantasy world, social withdrawal and neglected aspects of everyday life. In this paper, we report the case of a 16-year-old boy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The eight remaining studies employed a qualitative case study design ( Cuppone et al., 2021 ; Li et al., 2018 ; Niedermoser et al., 2021 ; Riley et al., 2022 ; Sachdeva & Verma., 2015 ; Sharma & Mahapatra., 2021 ; Siste et al., 2020 ; Torres-Rodríguez, Griffiths, Carbonell, Farriols-Hernando, & Torres-Jimenez, 2019 ) in which they presented in-depth, detailed, prolonged, and individualized examinations of the course of GD.…”
Section: Resultsmentioning
confidence: 99%
“…The eight remaining studies employed a qualitative case study design ( Cuppone et al., 2021 ; Li et al., 2018 ; Niedermoser et al., 2021 ; Riley et al., 2022 ; Sachdeva & Verma., 2015 ; Sharma & Mahapatra., 2021 ; Siste et al., 2020 ; Torres-Rodríguez, Griffiths, Carbonell, Farriols-Hernando, & Torres-Jimenez, 2019 ) in which they presented in-depth, detailed, prolonged, and individualized examinations of the course of GD.…”
Section: Resultsmentioning
confidence: 99%
“…Although mental health symptoms (e.g., depression and anxiety) are commonly investigated in relation to problematic Internet use (Bisen & Deshpande, 2018), maladaptive daydreaming, and the need to belong are rarely considered correlates of problematic technology use. However, maladaptive daydreaming shares some core features with behavioral addictions (see Somer, 2002) and has been associated with problematic Internet use (Zsila et al, 2018) and gaming disorder (Sharma & Mahapatra, 2021). The present study also found evidence for the positive association between maladaptive daydreaming and problematic Twitch use, suggesting that individuals with excessive daydreaming activity may be more prone to behavioral addictions.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential correlation could be maladaptive daydreaming, which involves excessive fantasizing, an activity that shares some common features with behavioral addictions (e.g., loss of control; Somer, 2002). Maladaptive daydreaming has been associated with problematic Internet use (Zsila et al, 2018) and gaming disorder (Sharma & Mahapatra, 2021). Moreover, excessive daydreaming was associated with disorders and problem behaviors on the impulsive–compulsive spectrum such as emotion regulation difficulties and prolonged immersion in rewarding activities, which are precursors of addictive use (Estévez et al, 2017; Koronczai et al, 2019).…”
Section: The Popularity Of Twitch and Current Research Perspectivesmentioning
confidence: 99%
“…"Maladaptive daydreaming" or "excessive daydreaming" is an increasingly recognized psychological phenomenon (Marcusson-Clavertz et al, 2019;Pietkiewicz et al, n.d.;Sharma & Mahapatra, 2021;Soffer-Dudek & Theodor-Katz, 2022;Somer et al, 2016 Oct-Dec). The term was first defined as "extensive fantasy activity that replaces human interaction and/or interferes with academic, interpersonal, or vocational functioning" (Somer, 2002).…”
Section: Applications To "Maladaptive Daydreaming"mentioning
confidence: 99%